1997
DOI: 10.1023/a:1018568308926
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Calcium hydroxyapatite bioceramic was toughened by preparing composites with silver particles as reinforcements. The composites were fabricated from hydroxyapatite and silver oxide raw powders. The sintering behaviour was investigated using dilatometry. An optimized sintering programme was designed to promote densification and to suppress the decomposition of the hydroxyapatite matrix and the evaporation of silver. High density was achieved on both small cylinder samples and large block samples by pressureless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Luckily, the histological evaluations revealed that HA/Ti biocomposites could be partially integrated with newborn bone tissues after 3 weeks and fully osteointegrated at 12 weeks in vivo [840]. Similar findings had been earlier made for HA bioceramics reinforced by addition of silver particulates (5-30 vol.%) and subsequent sintering of the HA/Ag powder compacts [838,839]. Other studies on calcium orthophosphate/Ti biocomposites are available elsewhere [845][846][847][848].…”
Section: Biocomposites With Glasses Inorganic Materials and Metalssupporting
confidence: 72%
“…Luckily, the histological evaluations revealed that HA/Ti biocomposites could be partially integrated with newborn bone tissues after 3 weeks and fully osteointegrated at 12 weeks in vivo [840]. Similar findings had been earlier made for HA bioceramics reinforced by addition of silver particulates (5-30 vol.%) and subsequent sintering of the HA/Ag powder compacts [838,839]. Other studies on calcium orthophosphate/Ti biocomposites are available elsewhere [845][846][847][848].…”
Section: Biocomposites With Glasses Inorganic Materials and Metalssupporting
confidence: 72%
“…%) and subsequent sintering of the HA/Ag powder compacts. 1028,1029 The addition of silver also imparts an antimicrobial activity. 1042 Other studies on calcium orthophosphate/Ti biocomposites are available elsewhere in reference 1035-1038. To conclude this section, biocomposites consisting only of calcium orthophosphates should be briefly described.…”
Section: Injectable Bone Substitutes (Ibs)mentioning
confidence: 99%
“…1003,1004 Various biocomposites of calcium orthophosphates with metals and alloys have been fabricated as well. 540,928,967,997,[1028][1029][1030][1031][1032][1033][1034][1035][1036][1037][1038][1039][1040][1041][1042][1043][1044][1045] For example, an HA-based biocomposite reinforced with 20 vol.% of Ti particles was fabricated by hot pressing. 1030 Calcium orthophosphate/Ti biocomposites might be prepared by powder metallurgy ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Several authors reported that HAP begins to be sintered at the temperatures between 700 and 800 °C, and several sintering temperatures between 1050 and 1250 °C were suggested by combining the dilatometric analysis with other characterization studies . Zhang et al reported that large shrinkage in the temperature range of 1000–1200 °C corresponds to a higher sintering rate, followed by a soaking period at 1250 °C where densification proceeded with a very slow sintering rate. Therefore, when dilatometric curve of the Ti–5HAP composite (Figure ) is considered together with the reported results in the literature, it might be suggested that the decrease observed on the shrinkage rate after about 915 °C may be related to the dehydration of HAP .…”
Section: Resultsmentioning
confidence: 99%